Blockchain Ready Port Supply Chain Using Distributed Ledger - Boison, David King; Antwi-Boampong, Ahmed (Nordic and Baltic Journal of Information & Communications Technologies, 2020)
Blockchain technology, as a bedrock for distributed ledgers, offers a platform for innovation for a new decentralized and transparent transaction machinery in industries and businesses, and the port is not an exception. The inbuilt features of this technology enrich trust through transparency and traceability within any transaction of data, goods, services, and financial resources. Notwithstanding initial doubts about this technology, lately government and large corporations have offered to adopt and enhance this technology in various fields of applications, from social and legal industries, and finance to design, maritime and port networks. In this paper, the authors review the current status of the Blockchain technology and some of its applications. The potential benefit of such a technology in port and maritime supply chain is then discussed, and a vision for the future Blockchain ready port and maritime supply chain are proposed. The importation of containerized vehicles is used as an example to demonstrate how such technology can be deployed in a global port industry. Finally, the requirements and challenges to adopt this technology in the future in relation to, port and maritime systems are discussed.